The Waste Free Movement to Support Sustainable Tourism in Bilebante Green Tourism Village - Nirwana, Baiq Nadia; Pratama, Aryan Agus; Talidobel, Susilo; Assa’ady, M. Chothibul Umam; Wardi, Putri Amalia (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
“Gerakan Merdeka Sampah” to Support Sustainable Tourism in the Green Tourism Village of Bilebante is a community development program aimed at promoting sustainable tourism in the Bilebante area. This program aims to reduce the volume of waste generated, raise community awareness about the importance of waste management, and create a healthy and safe environment. The implementation of this program involves several activities, including community development, preparation, cleaning, media campaigns, and community participation.